2017
DOI: 10.3389/fncir.2017.00083
|View full text |Cite
|
Sign up to set email alerts
|

Turtle Flexion Reflex Motor Patterns Show Windup, Mediated Partly by L-type Calcium Channels

Abstract: Windup is a form of multisecond temporal summation in which identical stimuli, delivered seconds apart, trigger increasingly strong neuronal responses. L-type Ca2+ channels have been shown to play an important role in the production of windup of spinal cord neuronal responses, initially in studies of turtle spinal cord and later in studies of mammalian spinal cord. L-type Ca2+ channels have also been shown to contribute to windup of limb withdrawal reflex (flexion reflex) in rats, but flexion reflex windup has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 61 publications
(117 reference statements)
0
12
0
Order By: Relevance
“…Two neuronal levels can elicit windup of their discharge within the flexion reflex circuit: motoneurons and DHNs [8,9,12,15,23]. We previously showed that, in control conditions, the windup of the flexion reflex was strictly correlated with DHNs windup [11].…”
Section: Neural Substrate Of Windupmentioning
confidence: 97%
See 1 more Smart Citation
“…Two neuronal levels can elicit windup of their discharge within the flexion reflex circuit: motoneurons and DHNs [8,9,12,15,23]. We previously showed that, in control conditions, the windup of the flexion reflex was strictly correlated with DHNs windup [11].…”
Section: Neural Substrate Of Windupmentioning
confidence: 97%
“…It has been shown that windup of the flexion reflex in juvenile rats depends on a synaptic balance between excitation and inhibition that allows expression of intrinsic properties [11,13,14]. However, the flexion reflex is the output of a neural circuit that comprises both DHNs and motor neurons, and the latter ones also exhibit a windup of their discharge that presents the same molecular sensitivity as windup of DHNs [8,9,15]. Because of the different model used (juvenile versus adult, turtles), the site of recordings (DHNs, motor neurons, and flexion reflex), our understanding of windup remains partial.…”
Section: Introductionmentioning
confidence: 99%
“…Two neuronal levels can elicit windup of their discharge within the flexion reflex circuit: motoneurone and DHNs neurons [8,9,12,15,23]. We previously showed that in control conditions, the windup of the flexion reflex was strictly correlated with DHNs windup [11].…”
Section: Neural Substrate Of Windupmentioning
confidence: 99%
“…It has been shown that windup of the flexion reflex in juvenile rats depends on a synaptic balance between excitation and inhibition that allow expression of intrinsic properties [11,13,14]. However, the flexion reflex is the output of a neural circuit that comprise both DHNs and motor neurons and the latter ones also exhibit a windup of their discharge that present the same molecular sensitivity as windup of DHNs [8,9,15]. Because of the different model used (juvenile versus adult, turtles), the site of recordings (DHNs, motor neurons, flexion reflex), our understanding of windup remains partial.…”
Section: Introductionmentioning
confidence: 99%
“…Such information can provide a foundation for constructing hypotheses and for comparison to species in which multifunctional and behaviorally specialized interneurons have been elucidated in more detail, especially hatchling Xenopus tadpoles and larval zebrafish (Berkowitz et al, 2010). The turtle spinal cord has been a focus of research on spinal control of multiple kinds of natural limb movements for Ͼ4 decades (Lennard and Stein, 1977;Valk-Fai and Crowe, 1978;Stein, 2018) and has also been a focus for investigation of diverse cellular-and circuit-level questions of general interest, including the ion channel mechanisms and modulation of plateau potentials, windup, and long-lasting excitability (Hounsgaard and Kiehn, 1989;Currie and Stein, 1990;Hounsgaard and Kjaerulff, 1992;Russo and Hounsgaard, 1994;Delgado-Lezama et al, 1997, 1999Russo et al, 1997;Guertin and Hounsgaard, 1998;Svirskis and Hounsgaard, 1998;Alaburda and Hounsgaard, 2003;Alaburda et al, 2005;Guzulaitis et al, 2013;Reali and Russo, 2013;Johnson et al, 2017), the contribution of rhythmic inhibition to spinal central patterngenerating networks (CPGs; Robertson and Stein, 1988;Berkowitz and Stein, 1994b;Berg et al, 2007;Berkowitz, 2008;Stein, 2010;Petersen et al, 2014;Guzulaitis and Hounsgaard, 2017), the distribution, sparseness, and modularity of spinal cord CPGs (Mortin and Stein, 1989;Stein et al, 1995Stein et al, , 1998Currie and Gonsalves, 1997;Stein, 2008;Guzulaitis et al, 2014;Hao et al, 2014;Radosevic et al, 2019)…”
Section: Introductionmentioning
confidence: 99%